Między tradycją a nowoczesnością - kodyfikacje polskiego prawa procesu cywilnego XX wieku - Demendecki, Tomasz (PRAWO i WIĘŹ, 2024)
The 20th century in the history of Polish law was the period of the creation of two Polish codes of civil procedure (1930, 1964). This article presents both of these procedural laws, in particular through the prism of the guiding principles of civil procedure. At the same time, it points to some universal challenges facing the national legislator, which remain valid today. Removing the features of civil procedural law specific to the socialist model in a modern state of law was and is now necessary due to the change in the conditions in which it applies. The search for a formula of a modern model of civil proceedings, the most effective and meeting the needs of the entities participating in it, continues to become a common trend.